Association between systemic immune-inflammation index and central obesity in pediatric populations: a cross-sectional and cohort study - Zhang, Qian; Kong, Bingxuan; Zhou, Zhiyu; Liu, Fangqu; Wen, Erya; Lin, Bingliang; Xuan, Peng; Lu, Wenlong; Su, Zhe; Li, Yanyan; Tang, Yuhan; Xiong, Jingfan; et al. (Frontiers in Immunology, 2025)
BackgroundCentral obesity in children represents a significant public health concern due to its strong association with an elevated risk of metabolic and cardiovascular disorders. The systemic immune inflammation index (SII) has been implicated in the pathophysiology of obesity-related chronic inflammation. Despite its potential relevance, the specific relationship between central obesity and SII in the pediatric population remains insufficiently explored. The objective of this study was to examine the relationship between SII and central obesity, with a particular focus on the potential of SII as a predictor of central obesity and a means of preventing obesity at an early stage of life.MethodsWaist-to-height ratio (WHtR), subcutaneous fat, and visceral fat were employed as obesity proxies. Central obesity was defined according to WHtR with a cutoff value of 0.46. The implications of SII on central obesity were examined in a sample of 4,730 individuals in 2021 and validated through a prospective study involving 1,425 subjects in 2023. Cross-sectional associations between SII and central obesity were examined using binomial logistic regression models and generalized linear models. The restricted cubic spline regression was used to explore the non-linear relationship between SII and obesity indicators. In a prospective study, we employed a modified Poisson regression model to investigate the potential causal relationship between SII and central obesity.ResultsCross-sectionally, adolescents in the highest quartile of SII levels exhibited the greatest risk for central obesity(OR=3.07, 95% CI:2.45~3.87) when compared to those in the lowest quartile. Subgroup analyses showed that higher SII was associated with central obesity. Longitudinally, individuals in the highest SII quartile were found to have the highest risk of developing central obesity (RR=1.83, 95% CI:1.18~2.83) over time.